Supporting AmeriCorps Volunteer Learning During the COVID-19 Pandemic: A Social Learning Perspective - Yinglin Ma (Journal of Public and Nonprofit Affairs, 2026)
Volunteers are the backbone of civil society, and learning can be critical to their engagement and to the quality of their service. However, the COVID-19 public health crisis was associated with a global decline in formal volunteering. This context highlights the need to understand how nonprofit leaders and volunteer administrators can sustain volunteer learning during a disaster period. Drawing on social learning theory and comparing datasets from four consecutive cohorts of AmeriCorps State and National volunteer members - two who served during the pandemic (2020 and 2021 members) and two before the pandemic (2018 and 2019 members), findings showed that those who served during the pandemic reported lower levels of learning outcomes. Nonetheless, perceptions of positive role models and helpful feedback attenuated this negative association, and community service self-efficacy mediated it. The findings support social learning theory and emphasize the importance of positive role modeling and constructive feedback as effective managerial practices for sustaining volunteer learning amid the operational and social disruptions.